Associations of Compassion Competence, Nursing Work Environment, Organizational Communication Satisfaction, and Missed Nursing Care on Patient Safety Among Nurses in Comprehensive Nursing Care Service Wards: A Path Analysis - SookHee Yoon (Healthcare, 2026)
Background/Objectives: This study aims to identify the factors associated with patient safety for nurses working in comprehensive nursing care service wards, based on the Structure–Process–Outcome model. As comprehensive nursing care service wards expanded in South Korea, the number of older and more severely ill inpatients increased, raising the demand for nursing care. In these wards, nurses play a crucial role in ensuring patient safety. Therefore, a thorough identification of the factors associated with patient safety, based on theoretical frameworks, is necessary. Methods: A cross-sectional design was used. Data were collected from 379 nurses working in one general hospital and four tertiary hospitals in South Korea between March and April 2022. Data were analyzed through descriptive statistics, Pearson’s correlation coefficient, and path analysis using SPSS 26.0 and AMOS 28.0. Results: Missed nursing care (β = −0.152, 95% confidence interval [CI]: −0.276 to −0.039) and nursing work environment (β = 0.150, 95% CI: 0.017 to 0.298) showed a direct association with patient safety. Compassion competence (β = 0.040, 95% CI: 0.009 to 0.092) and nursing work environment (β = 0.027, 95% CI: 0.006 to 0.069) were indirectly associated with patient safety through missed nursing care. The variables accounted for 18.7% of the explanatory power for patient safety. Conclusions: Missed nursing care was the factor most strongly associated with patient safety. Therefore, organizational efforts to foster a positive nursing work environment and implement strategies to enhance nurses’ compassion competence may further contribute to patient safety.